Students’ Reflective Thinking Ability in Solving Mathematics Problems Assessed From Students' Learning Style - Happy, Nurina; Setyowati, Khoirunisak; Utami, Rizky Esti (Journal of Mathematical Pedagogy (JoMP), 2021)
This study aims to describe students' reflective thinking skills in solving mathematics problems in terms of the learning styles of junior high school students. This type of research was descriptive qualitative research. The research subjects were students of class VIII at SMP Negeri 1 Candimulyo, Magelang Regency, in the academic year 2020/2021. The subjects of this study were 2 visual learning style students, 2 auditory learning style students, and 2 kinesthetic learning style students. Data collection techniques in this study were learning style questionnaires, tests of reflective thinking skills, and in-depth interviews. Triangulation in this study using source triangulation. The results of this study indicate that subjects with visual and auditory learning styles can meet the reflective thinking ability phase (Reacting, Comparing, and Contemplating) with each indicator being met so that the subject was at a reflective level. Kinesthetic learning style subjects were able to meet the reflective thinking ability phase (Reacting, Comparing, and Contemplating) but several indicators were not fulfilled, so the subject was at a fairly reflective level. Therefore, the profiles of students’ reflective thinking skills in visual and auditory learning styles were both at a reflective level, while the profiles of students' reflective thinking skills in kinesthetic learning styles were different because they were at a sufficiently reflective level.